Quality of life in a smoking cessation program: Lifestyle, anxiety, and depression - de FARIA, Daniela Junqueira [UNESP]; de ALMEIDA, Adriana Ávila [UNESP]; da SILVA, Igor Boaventura [UNESP]; Balducci, Ivan [UNESP]; Carta, Celina Faig Lima [UNESP]; Nicodemo, Denise [UNESP]; Almeida, Janete Dias [UNESP] (Editora Cubo, 2020)
Objective: Tobacco dependence is quite variable among individuals because it includes many aspects such as psychological, emotional, behavioral, and cultural perspectives. This study aimed to evaluate the social and emotional issues of patients in a smoking cessation program through the generic and specific quality of life questionnaires. Material and Methods: Two generic questionnaires (SF36 and Fantastic Lifestyle) and two specific (SRQ-20 for depression and STAI s/t for levels of state and anxiety trait) were applied at the first meeting and after three months of treatment. Data were statistically analyzed by the Pearson correlation coefficient (significance level of 5%). Results: In total, 15 participants (10 men, 5 women), with mean age of 60 and 56, respectively. The mean of the smoking intake was 65.88±34.37 for men and 35.66±11.17 for women. SRQ20 and STAI s/t indicated that poor improvement in depression and anxiety was related to relapse; SF36 questionnaire indicated improvement in the domains of physical aspect limit, pain, social and emotional aspects; Fantastic Lifestyle indicated improvement according to its scale, being in a first moment “Regular” (53 points), and later, “Good” (55.67 points). Conclusion: In conclusion, smoking cessation treatment is correlated to the decrease in anxiety and depression levels and improvement of the general quality of life.
Qualidade de vida em um programa de cessação do tabagismo: Estilo de vida, ansiedade e depressão
Keywords: Anxiety; Depression; Life style; Quality of life; Smoking cessation